Method of electrochemical biotesting for comparative analysis of probiotic and antibiotic properties of various plant extracts - V. S. Sibirtsev; U. Yu. Nechiporenko (Тонкие химические технологии)
Objectives. The purpose of this study was to develop an objective instrumental method for assessing microbial contamination and expressing the probiotic and antibiotic properties of food, pharmacological, and other products.Methods. The developed method consists of periodic (every 2 h) registration of changes in pH, redox potential, and electrical conductivity of a liquid nutrient medium incubated in the presence and absence of viable test microorganisms and test samples.Results. Using liquefied CO2 from 10 different types of plant materials, we carried out a comparative analysis of probiotic and antibiotic activities against Lactobacillus acidophilus of various concentrations of subcritical whole extracts obtained.Conclusions. Among the studied plant extracts, the most active prolonged antibiotic properties were exhibited by extracts from the leaves of Eucalyptus globulus Labill. and seeds of Illicium verum Hook.f. at a concentration in the test medium (CTE) more than 3 vol %, whereas the most active prolonged probiotic properties were exhibited by an extract from the herb of Mentha arvensis L. at CTE = 0.2 vol %. In most cases, the initial antibiotic activity of the tested extracts (TEs) was greater than their prolonged activity. Also, the mid-term (in terms of TEs interaction time with test microorganisms) antibiotic activity of TEs was intermediate in value between their initial and prolonged activity. In the test medium, the decreasing concentration of TEs decreases their antibiotic activity monotonically and increases their probiotic activity, suggesting that the biological activity of products, including various plant extracts, is largely determined not only by the raw material and the method of extracting biologically active substances from it but also by the concentration of the extract in the product and by the interaction time of the said product with microbiota and others. In most cases, a significant number of tests could establish the exact nature of these dependencies. The proposed method is much more rapid, objective, and informative and less laborious and material-intensive than using standard microbiological methods in assessing the initial microbial contamination and the probiotic and antibiotic properties of various samples of both the new and already approved pharmaceuticals, foods, and other products, as well as the individual ingredients and additives.